Does class participation predict academic achievement? A mixed-method study - Akpur, Uğur (English Language Teaching Educational Journal, 2021)
The present study’s aim is to identify whether class participation is a significant predictor of English language achievement among university students and their views concerning class participation and academic achievement. A sequential mixed method design was applied and a total of 2013 university students (813 female 40.3%; 1200 male, 59.7%) participated in the quantitative portion of the study. Course Participation Grade (CPG) criteria and English Proficiency Exam (EPE) held at the end of the academic year by the institution were used as data collection tools. The qualitative data were analysed through content analysis of a focus group interview with a group of seven participants. The findings suggested that the relationship between academic achievement and CPG was positive and significant. Correspondingly, the qualitative data revealed similar results with the quantitative data by showing that the class participation has powerful impact on academic achievement.